Stand Structure Dynamic of Logged Over Forest after Selective Timber Harvesting in Boven Digoel, Papua - Fitriana Wulansari Permata; Budi Kuncahyo; Haruni Krisnawati; Relawan Kuswandi (Department of Forestry, Faculty of Agriculture, University of Lampung, 2023)
Logged-over natural forest has a different stand structure and composition from primary natural forest due to logging activities. This study aimed to examine forest dynamics (upgrowth, ingrowth, and mortality) of the logged-over forest in PT. Tunas Timber Lestari (TTL) Papua in both stands with and without treatments. The data used in this study were based on the measurement in the Permanent Measurement Plots (PUP) for ten years. This study grouped data into five diameter classes of 10 cm intervals and three wood species groups (meranti timber, mixed timber, and non-commercial timber). Data analysis was carried out by forming a stand structure model and calculating the rate of ingrowth, upgrowth, and mortality. The stand structure model for each species group in stands with treatment had a significant R² value compared to those without treatment. The average ingrowth rate in the stands with treatment was smaller than without treatment. The values of upgrowth varied with the increase in diameter classes for both stands with and without treatments. The mortality rate in stands without treatment tended to be higher, especially in mixed timber and non-commercial timber groups. In contrast, in the meranti timber group, the mortality rate mostly occurred in the stands with treatment. The stand structure models resulting in this study can be used as important information in determining appropriate silvicultural options for forest stands. Keywords: Forest dynamics, logged-over forest, meranti, selective logging